2005
DOI: 10.1016/j.ydbio.2005.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Prox1 activity controls pancreas morphogenesis and participates in the production of “secondary transition” pancreatic endocrine cells

Abstract: The development of the mammalian pancreas is governed by various signaling processes and by a cascade of gene activation events controlled by different transcription factors. Here we show that the divergent homeodomain transcription factor Prox1 is a novel, crucial regulator of mouse pancreas organogenesis. Loss of Prox1 function severely disrupted epithelial pancreas morphology and hindered pancreatic growth without affecting significantly the genesis of endocrine cells before E11.5. Conversely, the lack of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
96
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 41 publications
7
96
0
2
Order By: Relevance
“…By E13.5, it is expressed in Ngn3 + endocrine progenitors. Finally, from E15.5, Prox1 is specifically expressed in endocrine, ductal and centroacinar cells, while it is excluded from acinar cells (Wang et al, 2005).…”
Section: Prospero-related Homeobox Transcription Factor1 (Prox1)mentioning
confidence: 99%
“…By E13.5, it is expressed in Ngn3 + endocrine progenitors. Finally, from E15.5, Prox1 is specifically expressed in endocrine, ductal and centroacinar cells, while it is excluded from acinar cells (Wang et al, 2005).…”
Section: Prospero-related Homeobox Transcription Factor1 (Prox1)mentioning
confidence: 99%
“…Prox1 homologues have been identified in other vertebrates, including Xenopus, zebrafish, chicken, and human (Tomarev et al, 1996;Glasgow and Tomarev, 1998;Ny et al, 2005). In vertebrates, Prox1 is expressed in the developing neural retina, lens, cochlea, spinal cord, brain, skeletal muscle, heart, liver, pancreas, and in the endothelial cells that will give rise to the lymphatic vasculature (Oliver et al, 1993;Tomarev et al, 1996;Glasgow and Tomarev, 1998;Burke and Oliver, 2002;Wigle et al, 2002;Wang et al, 2005;Bermingham-McDonogh et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In mice, functional inactivation of Prox1 demonstrated that this gene's activity is critical for the formation of a variety of organs and cell types, including the lens, retina, liver, pancreas, and lymphatic endothelial cells Sosa-Pineda et al, 2000;Hong et al, 2002;Dyer et al, 2003;Harvey et al, 2005;Wang et al, 2005). In Drosophila, prospero is a cell-fate determinant in the asymmetric divisions of neuroblasts (Doe et al, 1991;Vaessin et al, 1991) and is required to maintain the mitotic potential of glial cells (Griffiths and Hidalgo, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These defects were attributed to a non-cell-autonomous function for Cdc42 in positioning initially multipotent progenitors within environments conducive for endocrine differentiation. Finally, tissue-specific inactivation of transcription factors expressed in the trunk-such as HNF6 (Pierreux et al 2006), Prox1 (Wang et al 2005;Westmoreland et al 2012), or HNF1b (De Vas et al 2015-results in epithelial malformations and concurrent deficits in endocrine differentiation. While these outcomes are interpreted largely on the basis of upstream transcriptional effects on Ngn3, they are consistent with the idea that misregulated epithelial morphology precludes efficient engagement of the endocrine differentiation program.…”
mentioning
confidence: 99%